YAMI KAWAII STYLE VISUAL SIGN STUDY - Mestika Nawang Sukma (JURNAL PAKARENA, 2021)
The function of today’s fashion is not only as a cover of the body for the sake of modesty, but as a way of communicating. Fashion communication can be conveyed through clothing, costumes, and make-up which associated with the latest issues, such as mental health. WHO revealed that 450 million people in the world had suffer from mental disorders, and more than 150 million people have experience depression. The issue of fashion and mental health gave birth to a subculture in Japan called Yami Kawaii. Yami Kawaii is a fashion style that represents a depressive style of clothing with a cute touch. Dressing in the Yami kawaii style is a way for some people to send a message to others that they are suffering from a psychological or mental disorder that is shown through the clothes they wear. This study aims to see visual signs in the Yami Kawaii style as a representation of mental health. This study uses visual analysis with an element of fashion theory approach with six (6) elements of fashion, including: (1) Silhouettes, (2) Lines, (3) Details, (4) Fabric, (5) Motifs, (6) Colors. The results of this study indicate that the overall style of Yami Kawaii contains 6 elements of fashion to deliver the messages about mental health issue.